Renovation and modernisation of a postindustrial facility in Poznań = Renowacja z modernizacją budynku poindustrianlego w Poznaniu - Błaszczyński, Tomasz; Wielentejczyk, Przemysław; Błaszczyński, Maciej; Pijanowski, Filip (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a renovation process of a historic postindustrial building situated on premises of Gazownia Poznańska. An unprepared team of designers made a lot of mistakes and negligences, which led to additional work, repairs including. The increased scope of work also led to a substantial increase in the cost of the carried out renovations. The modernisation process was realised with the use of modern technologies, some of which for the first time in Poznan.
Keywords: budynek poindustrialny; renowacja; modernizacja; renovation; modernisation; jet grouting; helifix